Técnica de hall en lesiones cariosas en molares temporales: Revisión bibliográfica - Gonzalez Loja, Tatiana Maribel (2024)
Advances in restorative dentistry and dental materials have led to increasingly conservative approaches to the treatment of carious lesions. In the meantime, methods such as the Hall technique have been used. The aim of this study is to determine the protocol and the effectiveness of the Hall technique in the treatment of primary molars affected by carious lesions. This study involves an integrative literature review conducted through systematic searches of bibliographic databases, including PubMed, the Virtual Health Library (VHL), Scielo, Google Scholar, among others. A total of 20 scientific articles that met the pre-defined inclusion criteria are included. Tables designed in Microsoft Excel are used to organize the data to meet the research objectives. Regarding the protocol, the authors agree that it should be performed in two sessions. Thus, the results show that the Hall technique has produced excellent results over the years, with a success rate of 90% at the two-year clinical and radiographic follow-up. In relation to the behavior of children, it is less traumatic, with a 100% acceptance rate considered satisfactory by both parents and dentists, especially pediatricians. Based on the literature, the clinical and radiographic efficacy of the Hall technique is demonstrated, with favorable results for the control of carious lesions in primary molars